The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1002/marc.200800756
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Core‐Shell Nanoparticle Formation by Two‐Dimensional Nuclear Magnetic Resonance

Abstract: We have studied the kinetics of polymeric nanoparticle formation for poly(styrene-block-4-vinylpyridine) [P(S-b-4-VPy)], chains in a non-selective solvent using 1,4-dibromobutane (DBB) as a cross-linker by means of different nuclear magnetic resonance (NMR) spectroscopy techniques. The kinetic process was followed using (1) H, (13) C, and 2-D Heteronuclear Single Quantum Correlation (HSQC) NMR experiments. The kinetic data obtained from 2-D HSQC and (1) H NMR experiments were in good agreement between them, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Furthermore, in the same group of spectra, a signal at δ = 8.3 ppm corresponding to the proton (NÀCHÀ) of P2VP that was a doublet at low reaction time became a singlet when time of reaction increased. Ruiz de Luzuriaga et al 41 reported similar behavior in the quaternization of poly (4-vinylpyridine). This variation of the spectra was attributed to reduction of mobility of monomeric units during the quaternization reaction.…”
Section: ' Resultsmentioning
confidence: 82%
“…Furthermore, in the same group of spectra, a signal at δ = 8.3 ppm corresponding to the proton (NÀCHÀ) of P2VP that was a doublet at low reaction time became a singlet when time of reaction increased. Ruiz de Luzuriaga et al 41 reported similar behavior in the quaternization of poly (4-vinylpyridine). This variation of the spectra was attributed to reduction of mobility of monomeric units during the quaternization reaction.…”
Section: ' Resultsmentioning
confidence: 82%
“…Furthermore, the doublet observed at δ = 8.3 ppm corresponding to the proton (N–CH−) of P2VP at short reaction time (or low conversion) became a singlet at longer reaction time (or higher conversion). Ruiz de Luzuriaga et al reported similar behavior during the quaternization of poly(4-vinylpyridine) which was attributed to the mobility reduction of monomeric units after quaternization. 1 H NMR was used to monitor the kinetics of quaternization of poly( 0 ).…”
Section: Resultsmentioning
confidence: 84%